2003
DOI: 10.1002/abio.200390018
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence Biosensor for the Detection of Organomercury Contamination

Abstract: To selectively detect organomercurial compounds in the environment, in this study a bioluminescence biosensor for organomercurials was developed using a bacterial gene expression system for the mercury resistance determinant. merB 3 -Luciferase (mer-lux) transcriptional fusion plasmids pHYΒ3Lux and pHY∆Β3Lux were constructed to evaluate the gene expression system with a new organomercury lyase gene merB 3 from Bacillus megaterium strain MB1, which is resistant to a broad spectrum of mercury compounds, and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 19 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…This is consistent with the mechanism of passive diffusion. The plasmid pDES1 is a slight improvement on the design of Endo et al (8), who reported a detection limit of 50 nM for phenylmercury acetate, an organomercurial compound. A 1-to 2-order-of-magnitude improvement in the detection limit allows the examination of bioavailability at concentrations closer to those found in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the mechanism of passive diffusion. The plasmid pDES1 is a slight improvement on the design of Endo et al (8), who reported a detection limit of 50 nM for phenylmercury acetate, an organomercurial compound. A 1-to 2-order-of-magnitude improvement in the detection limit allows the examination of bioavailability at concentrations closer to those found in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…In order to effectively determine organomercurial compounds using a mer-lux plasmid bioreporter, it is necessary to convert organomercurials to Hg 2ϩ . Endo et al (8) incorporated the gene merB into a similar design of a mer-lux plasmid bioreporter (pHYB3Lux) and showed that the detection limit of this new bioreporter for phenylmercury acetate ranged from 50 nM to 5 M. MerB catalyzes the breakdown of phenylmercury and CH 3 Hg(II) to Hg 2ϩ (2,26), which binds to MerR, thereby switching on the lux system. In this study, we attempted to develop a similar biosensor/bioreporter that can quantify the amount of CH 3 Hg(II) that has entered a cell from the medium and to use the biosensor to investigate the impacts of chloride and different forms of NDOM, such as thiols and humic acids, on the bioavailability of CH 3 Hg(II) in bacterial cells.…”
mentioning
confidence: 99%
“…The Nobel Prize in Chemistry of 2008 was awarded to Osamu Shimomura, Martin Chalfie and Roger Tsien as a recognition of their research on the green fluorescent protein (GFP). Bioluminescence has already found successful applications in different fields, such as gene expression,1 biosensors for environmental pollutants,2 and cancer monitoring 3. Among the bioluminescence systems, the firefly luciferin–luciferase system is one of the most widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…The testing medium in this research was completely LB (primitive cell culture or LB diluted sample). Medium composition might affect mercury bioavailability for a bacterial strain, and reduce the sensitivity of the luminescence test, thus changing to an appropriate medium would be helpful to achieve a lower detection limit (Barkay et al, 1997;Endo et al, 2003;Rasmussen et al, 2000;Thouand et al, 2003).…”
Section: Sensitivity and Specificity Of Pthe30-e Colimentioning
confidence: 99%